2004
DOI: 10.1186/1471-2296-5-28
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers' practices, knowledge and beliefs of antibiotics in paediatric upper respiratorytract infections in Trinidad and Tobago: a cross-sectional study

Abstract: Background: Antibiotic overuse and misuse for upper respiratory tract infections in children is widespread and fuelled by public attitudes and expectations. This study assessed knowledge, beliefs, and practices regarding antibiotic use for these paediatric infections among children's caregivers' in Trinidad and Tobago in the English speaking Caribbean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 30 publications
8
83
3
2
Order By: Relevance
“…Other factors such as the economic interests of drug manufacturers, hospitals and other sectors, and loopholes in the regulation are the identified by the participants as contributors to ABR in Sri Lanka. Similar findings have been seen from other studies around the globe [20,21].…”
Section: Knowledge About Antibioticssupporting
confidence: 92%
See 1 more Smart Citation
“…Other factors such as the economic interests of drug manufacturers, hospitals and other sectors, and loopholes in the regulation are the identified by the participants as contributors to ABR in Sri Lanka. Similar findings have been seen from other studies around the globe [20,21].…”
Section: Knowledge About Antibioticssupporting
confidence: 92%
“…This may be complicated by the availability of antibiotics without prescription (regulated but not controlled) [17][18][19] and lack of laboratories for antibiotics susceptibility testing and surveillance. Factors such as; lack of access to health care services, services are not affordable, limited regulatory control of the use of prescription medicines including antibiotics, limited understanding of the role of antibiotics, the opportunity to self-medicate, the concern of doctors for the risk of secondary bacterial infections after viral illnesses in poor environments, prohibitive cost sensitivity testing and pharmaceutical promotional tactics all compound the problem [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Groups with inadequate knowledge regarding antibiotic use included the elderly (aged ≥ 60), and those of lower socioeconomic or educational status. As we found, a higher educational level has been associated with better knowledge and attitude (Parimi, Pereira, & Prabhakar, 2004;Van den Eng et al, 2003;You et al, 2008), and the elderly are less knowledgeable about antibiotics in general (McNulty et al, 2007a). A unique finding in our study was that respondents aged ≥ 60 had better attitudes than those aged 40-59, even though their knowledge of antibiotics was the lowest overall.…”
Section: Discussionmentioning
confidence: 47%
“…Parimi et al (2004) found that the antibiotic knowledge score did influence attitude and behavior. In that study, demanding antibiotic prescriptions and keeping these drugs at home to treat illness was higher in respondents with inadequate knowledge than in those with adequate knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…18 Another interesting fact is the availability of health insurance that is reported to be associated with low antibiotic misuse with better knowledge, beliefs and practices. 19 In Saudi Arabia, health care is available with a better health care insured for the population and where antibiotic misuse is lower as in developed settings; the knowledge beliefs and practices need to be enhanced. Our study had several strengths, first, use of parents (mothers and fathers) as a target population to obtain direct information no knowledge, beliefs and practices.…”
Section: Resultsmentioning
confidence: 99%